2023
DOI: 10.1097/nne.0000000000001410
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simulated Telenursing With Standardized Patients to Enhance Prelicensure Nursing Education

Abstract: Background: Telenursing is a growing field in health care but remains underutilized as a clinical learning opportunity in the prelicensure nursing curriculum. Problem: Prelicensure nursing students need exposure to telenursing as an educational modality, which can serve as an alternative opportunity for clinical hours where facilities and resources are limited. Approach: Using standardized patients and a web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…In total, 2 studies focused on NI education [ 85 , 86 ]. Of note, some of these interventions were implemented or developed in response to the COVID-19 pandemic [ 32 - 36 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 2 studies focused on NI education [ 85 , 86 ]. Of note, some of these interventions were implemented or developed in response to the COVID-19 pandemic [ 32 - 36 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Integration of simulation experiences was mostly as a stand-alone intervention; a few studies reported integration as part of an existing course. These studies integrated the simulation experiences as part of a rotation practice [ 38 ], course assignment [ 33 ], and as part of a clinical course [ 37 , 40 ]. Simulation was delivered mainly via teleconferencing and online technologies such as Zoom and Google Hangouts [ 32 , 33 , 35 , 36 , 40 - 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations